The extent to which the tools of educational evaluation of mathematics are applied in the Algerian secondary education stage according to the approach of competencies- reality and challenges - Bentahar , Salim; Merzag, Merzag (Al-Jamie Journal In Psychological Studies and Educational Sciences, 2021)
Specialists in the educational field consider mathematics as an indicator to indicate the level of scientific thinking of the learner because it contains appropriate levels of knowledge to determine the student’s academic achievement level and to rely on measurement and evaluation tools that the professor uses in measuring the level of students ’performance and achievement. Therefore, the researcher felt that there is a problem in applying measurement tools. Educational studies in line with the contemporary challenges of developing education systems, the study aims to identify the reality of applying educational evaluation tools for the subject in Algerian secondary education institutions, which face the most important difficulties facing the educational assessment and evaluation process according to the competency approach and opens the way for research into the extent of application of measurement and evaluation theories Pedagogical in mathematics achievement in Algerian secondary education institutions.The results confirm that the majority of professors tend to adopt the written exam as the only method for educational measurement, despite their application of other methods of measurement such as observation and performance testing due to a set of pedagogical and organizational difficulties. It also stresses the necessity of training a teacher in building tests according to their types, taking into account good test specifications according to the student’s knowledge levels, as well as training them in methods and methods of educational measurement and evaluation of the educational material according to standards that are compatible with modern educational measurement and evaluation tools.